Restorative Justice and Criminal Law Reform: Global Trends and Policy Implications - Muhammad Mpu Samudra (AKADEMI TEKNIK ADI KARYA, 2025)
Restorative justice has developed into one of the most significant approaches in criminal law reform in various countries, particularly in response to the limitations of the retributive justice model, which is considered ineffective in tackling crime and restoring social relations. This article analyzes global trends in the application of restorative justice and its policy implications in the context of modern criminal law reform. Through a comparative study of policies in a number of jurisdictions, including Europe, North America, and the Asia-Pacific region, this study identifies patterns of application that include the expansion of sentencing alternatives, strengthening victim participation, and integrating penal mediation mechanisms. The findings show that countries that systematically adopt restorative justice tend to experience increased victim satisfaction, lower recidivism rates, and higher case resolution effectiveness, despite still facing institutional barriers, differences in implementation standards, and cultural resistance within law enforcement agencies